An Analysis of Task-Based Learning to Improve English Language Education Students’Grammar Mastery - Ni Made Dita Sintadewi; Kadek Lina; Made Detri Suryantini (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the implementation of Task-Based Learning in grammar class of third-semester English Language Education students at Triatma Mulya University. The study also investigates students’ responses toward the implementation of Task-Based Learning during learning process. A qualitative descriptive method was used, which involved classroom observations, interviews, and documentation. The results show that 1) Task-Based Learning increases students’ motivation in learning grammar, 2) Task-Based Learning makes the students more confident in using grammar, 3) Task-Based Learning can improve students’ participation during classroom activities, 4) Task-Based Learning helps students to learn grammar easily and clearly. The study concludes that Task-based Learning has significance influence in improving students’ grammar mastery. Task-Based Learning can be considered as an effective approach for teaching grammar in English Language Education classes.